المؤاخاة بين المهاجرين والأنصار:القيم والمبادئ وإمكانية الاستفادة في عصر العولمة: Brotherhood between the Muhājirūn and the Anșār: Values, Principles, and Potential Benefits in the Age of Globalization - Aman ullah, Bi Bi Saima; Ullah, Dr. Sami; Ahmad, Dr. Manzoor (Al-Amīr Research Journal for Islamic Studies, 2024)
This article examines the concept of brotherhood (المؤاخاة) between the Muhajirun (emigrants) and the Ansar (helpers) during the early Islamic period, focusing on its principles, foundations, and contemporary applications. The brotherhood established by the Prophet Muhammad (صلى الله عليه وسلم) created a model of solidarity and social cohesion that remains relevant today.In the religious domain, these principles can enhance unity among Muslims by promoting shared values and organizing cultural and religious activities. Economically, the model advocates for justice and social equity through fair wealth distribution, zakat, and charitable initiatives, which can reduce economic disparities and support sustainable development. Scientifically, the principles of brotherhood encourage collaborative research and knowledge exchange. Establishing joint research centers and academic programs can elevate scientific and technological capabilities in Muslim countries, contributing to global progress. In facing globalization challenges, the brotherhood model offers solutions for preserving cultural and religious identities while promoting social and economic equity. It supports political and diplomatic cooperation to defend shared interests and achieve sustainable development. In conclusion, the brotherhood between the Muhajirun and the Ansar provides timeless lessons in unity, justice, and cooperation, offering valuable insights for addressing modern challenges and fostering progress in various fields. Keywords: Brotherhood, Muhajirun, Ansar, solidarity, contemporary applications.